Faktor Penentu Kinerja Manajerial: Studi Pada Perguruan Tinggi Negeri di Jakarta - Efrida Yasni Nasution; Hermiyetti Hermiyetti (Faculty of Economic and Business, 2017)
Determine Factor of Managerial Performance: Study at State University in JakartaThis study aims to analyse the influence of budget participation and role conflict on managerial performance, how professional orientation can moderate the relationship of budget participation and role conflict on managerial performance. This study has selected 66 lecturers from three universities (UI, UNJ dan UIN Jakarta). The data collected were analyzed using Moderated Regression Analysis (MRA). The research has resulted in the following conclusions: The budget participation does not affect the performance of managerial, The professional orientation functions as moderating variables (pure moderator) to strengthen the relationship between budgetary participation on managerial performance, The role conflict is influential on managerial performance and the professional orientation functions as moderating variables (quasi-moderator) so as to strengthen the relationship between role conflict and managerial performance.DOI: 10.15408/ess.v7i2.4916